Analisis Penerapan Perilaku Hidup Bersih dan Sehat (PHBS) di TK Pembina HKBP Tarutung. - Lisma Br Manik; Emmi Silvia Herlina; Ledyana Dwi Mei Situngkir; Mei Lastri E.F. Butar Butar; Rotua Samosir (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to describe the implementation of Clean and Healthy Living Behavior (PHBS) at TK Pembina HKBP Tarutung and to analyze the roles of the principal, teachers, and parents in supporting the implementation of the program. This research uses a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. Data analysis was conducted thru the stages of data reduction, data presentation, and drawing conclusions.The research results show that the implementation of PHBS at TK Pembina HKBP Tarutung has been carried out systematically, *planned, and continuously.The principal acts as the policymaker and program supervisor, teachers are the main implementers in guiding children in daily activities, while parents participate in continuing clean living habits at home. The PHBS activities implemented include washing hands with soap, choosing healthy snacks, using clean toilets, exercising regularly, eliminating mosquito larvae, weighing and measuring height regularly, and disposing of waste in the proper place. Overall, the implementation of PHBS at TK Pembina HKBP Tarutung has created a healthy school environment and instilled positive habits in children from an early age.